177Lu-Dendrimer Conjugated to Folate and Bombesin with Gold Nanoparticles in the Dendritic Cavity: A Potential Theranostic Radiopharmaceutical. (16th August 2016) - Mendoza-Nava, Héctor; Ferro-Flores, Guillermina; Ramírez, Flor de María; Ocampo-García, Blanca; Santos-Cuevas, Clara; Aranda-Lara, Liliana; Azorín-Vega, Erika; Morales-Avila, Enrique; Isaac-Olivé, Keila
Abstract : 177 Lu-labeled nanoparticles conjugated to biomolecules have been proposed as a new class of theranostic radiopharmaceuticals. The aim of this research was to synthesize 177 Lu-dendrimer(PAMAM-G4)-folate-bombesin with gold nanoparticles (AuNPs) in the dendritic cavity and to evaluate the radiopharmaceutical potential for targeted radiotherapy and the simultaneous detection of folate receptors (FRs) and gastrin-releasing peptide receptors (GRPRs) overexpressed in breast cancer cells. p-SCN-Benzyl-DOTA was conjugated in aqueous-basic medium to the dendrimer. The carboxylate groups of Lys 1 Lys 3 (DOTA)-bombesin and folic acid were activated with HATU and also conjugated to the dendrimer. The conjugate was mixed with 1% HAuCl4 followed by the addition of NaBH4 and purified by ultrafiltration. Elemental analysis (EDS), particle size distribution (DLS), TEM analysis, UV-Vis, and infrared and fluorescence spectroscopies were performed. The conjugate was radiolabeled using 177 LuCl3 or 68 GaCl3 and analyzed by radio-HPLC. Studies confirmed the dendrimer functionalization with high radiochemical purity (>95%). Fluorescence results demonstrated that the presence of AuNPs in the dendritic cavity confers useful photophysical properties to the radiopharmaceutical for optical imaging. Preliminary binding studies in T47D breast cancer cells showed a specific cell uptake (41.15 ± 2.72 %). 177 Lu-dendrimer(AuNP)-folate-bombesin may be useful as an optical and nuclear imaging agent for breast tumors overexpressing GRPR and FRs, as well as for targeted radiotherapy.